1995
DOI: 10.1021/bp00032a011
|View full text |Cite
|
Sign up to set email alerts
|

Dichloroethane Removal from Gas Streams by an Extractive Membrane Bioreactor

Abstract: A novel extractive membrane bioreactor (EMB) system, in which a silicone rubber membrane separates a contaminated gas stream from an aerated biomedium, extracted and biodegraded 1,2‐dichloroethane (DCE) from a gaseous waste stream. Selective transfer of the organic compound takes place through the silicone membrane to the biomedium, where biodegradation occurs. At a gas flow rate of 770 mL min−1 and an average DCE concentration of 0.65 mg L−1, the EMB, with 2.5 m2 of membrane surface contained in a spirally wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 7 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Several studies have reported the performance decline caused by biofilm growth. Dos Santos et al 23 attributed the decreasing reactor performance and increasing pressure drop over the liquid phase to extensive biofilm formation. Reij and Hartmans24 also observed a clogging of hollow‐fiber MBR with a biofilm of propene‐degrading Xanthobacter cells over of period of 3–6 months.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported the performance decline caused by biofilm growth. Dos Santos et al 23 attributed the decreasing reactor performance and increasing pressure drop over the liquid phase to extensive biofilm formation. Reij and Hartmans24 also observed a clogging of hollow‐fiber MBR with a biofilm of propene‐degrading Xanthobacter cells over of period of 3–6 months.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with nonporous PDMS tubular membranes, the thickness of the non-porous PDMS layer on a substrate was decreased significantly, and resultant phenol mass transfer coefficients significantly increased to 4.1-6.5 m$s -1 [197,198]. These findings make EMBR suitable to treat inorganicorganic composite wastewater [199][200][201] Compared with conventional MBR with UF/MF membranes, MBR with NMBR (Fig. 8) can further improve solute rejection and enhance the quality of produced water.…”
Section: Embrmentioning
confidence: 97%
“…to aliphatic compounds (e.g. dichloroethane [52,56], 1,3-dichloropropene [57] and dichloromethane [58,59]). Most of these compounds studied are hydrophobic or marginally soluble organic chemicals.…”
Section: Embr Applications and Challengesmentioning
confidence: 99%
“…Most of these compounds studied are hydrophobic or marginally soluble organic chemicals. The EMBR application for treatment of wastewaters containing volatile organic compounds (VOCs) has been successfully extended to treating VOC-contaminated waste gases, and superior volumetric removal efficiency has been achieved compared to an alternative bioscrubbing process [56]. A variation of the EMBR used an anaerobic bioprocess to treat tetrachloroethene in a synthetic wastewater [60].…”
Section: Embr Applications and Challengesmentioning
confidence: 99%